ON THE RESULTS OF THE SPECIAL PRESIDENTIAL ELECTIONS IN GEORGIA - TCHANTOURIDZE, Lasha (CENTRAL ASIA AND THE CAUCASUS, 2008)
The 5 January 2008 snap poll was the first ever truly competitive presidential election in Georgia. The incumbent, Mikhail Saakashvili, just managed to retain his seat, narrowly avoiding a run-off with the main opposition candidate, Levan Gachechiladze. According to the Central Electoral Commission (CEC) of Georgia, and the exit polls commissioned by government-controlled television companies, Saakashvili received between 50.8 and 54 percent of votes, while Gachechiladze stayed below 30 percent.local and international observers have noted numerous irregularities, but overall, they have endorsed the elections as democratic. Opposition parties, however, have been less than convinced in fairness of the results as they have insisted that the current outcome is, indeed, a result of the noted irregularities. The snap presidential poll is a step forward for Georgian democracy, with credible opposition now emerging in the country. Both Saakashvili and the main opposition camps have made some gains. The main set-back for democracy was the suppression of Imedi TV, the only nongovernment controlled nationwide television channel. The January 2008 poll was the culmination of a very tense stand-off between the government and the opposition, which started in September 2007 with shocking revelations from a former defense minister Okruashvili. The stand-off reached its climax on 7 November 2007, when the special forces of the Ministry of Interior brutally dispersed a mass